Religion in our daily lives: Self-interpretation as a form of philosophical counselling - Hagiu, Adrian (Journal for the study of religions and ideologies, 2023)
In the present paper we propose a preliminary discussion on the narrative identity underlying the constitution of the self in the thought of the French philosopher Paul Ricœur by relating his hermeneutics of the self to philosophical counseling, which implies the need to discuss the respondent self in the face of sacred texts. The goal of self-understanding and thereby of (self-)counselling is the pursuit of a fulfilled life. Therefore, we provide an outline of how the IPAA method of philosophical counselling can be implemented in relation to religion’s contribution to everyday life. In the light of these objectives, we substantiate the thesis that self-interpretation is in fact self-understanding, and this self-understanding is enhanced by ‘putting’ the self face to face with sacred texts. The main purpose of the present study is to illustrate how the IPAA method can be applied to existential problems, and thus to highlight the following practical implications: (1) a description of the existential or intellectual contribution that sacred texts bring to self-interpretation, and ultimately to self-understanding; (2) an outline of how the IPAA method of philosophical counselling can be practically applied, and this we have done by observing that the role of the philosophical counsellor, when it comes to religious problems, can be readily assumed by a priest, a pastor, and so on, and hence its importance in counselling environments.